2018
DOI: 10.1038/s41524-018-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Computational discovery of p-type transparent oxide semiconductors using hydrogen descriptor

Abstract: The ultimate transparent electronic devices require complementary and symmetrical pairs of n-type and p-type transparent semiconductors. While several n-type transparent oxide semiconductors like InGaZnO and ZnO are available and being used in consumer electronics, there are practically no p-type oxides that are comparable to the n-type counterpart in spite of tremendous efforts to discover them. Recently, high-throughput screening with the density functional theory calculations attempted to identify candidate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
79
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(83 citation statements)
references
References 41 publications
4
79
0
Order By: Relevance
“…In contrast, previous first-principles studies on the p-type dopability of β-Ga 2 O 3 have revealed a lack of shallow acceptors [15,16] and formation of self-trapped holes (STHs) [17][18][19], both of which hinder efficient p-type doping. Apart from exceptions including Cu (I) and Sn (II) oxides, the upper valence bands of oxides are mainly composed of O 2p orbitals and have small energy dispersions compared with other compounds such as nitrides, phosphides, and arsenides [20][21][22][23][24][25][26]. The relatively localized valence states could lead to STH formation and, therefore, low-hole mobility [17].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, previous first-principles studies on the p-type dopability of β-Ga 2 O 3 have revealed a lack of shallow acceptors [15,16] and formation of self-trapped holes (STHs) [17][18][19], both of which hinder efficient p-type doping. Apart from exceptions including Cu (I) and Sn (II) oxides, the upper valence bands of oxides are mainly composed of O 2p orbitals and have small energy dispersions compared with other compounds such as nitrides, phosphides, and arsenides [20][21][22][23][24][25][26]. The relatively localized valence states could lead to STH formation and, therefore, low-hole mobility [17].…”
Section: Introductionmentioning
confidence: 99%
“…4,5,6 This discovery shifted the research interest from intrinsic defects to reactive impurities and their impact on the defect stability and materials properties in general. 4,7,8 Owing to the fully occupied orbitals, it is intuitively thought that noble gases remain inert during the interaction with various materials. Therefore, it is a common belief that the presence of a noble gas (e.g., Ar) during sputtering or wet-chemical synthesis inside a glove box does not affect properties of the product material.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, though n‐type WBGSs (e.g., ZnO, Ga 2 O 3 , and AlGaN) with good conductivity and stability can operate in the UV and DUV range (280−390 nm), it is not possible to convert them to a p‐type material with good stability and conductivity due to their intrinsic electronic properties . Consequently, no highly stable conductive p‐type DUV WBGS operating in both UV‐B and UV‐C region presently exists …”
mentioning
confidence: 99%